Opportunities and Challenges for the Development of the Office Furniture Industry: A Case from China - Sijie Fu; Ruiying Wan; Xianqing Xiong (BioResources, 2025)
The office furniture industry plays a pivotal role in shaping modern work environments, reflecting broader trends in industrial development and the diffusion of innovation. However, it faces significant imbalances globally – particularly in developing countries – such as fragmented competition, limited intelligent manufacturing capabilities, and weak brand recognition. Taking China as a representative case, this study employed a mixed-methods approach combining bibliometric analysis, industry interviews, and SWOT analysis to explore the current status, key challenges, and future directions of the office furniture sector. The results show that while China has become a global manufacturing hub with mature supply chains and cost advantages, it still lags in brand influence, design innovation, and environmental sustainability. The evolving demands for ergonomic, modular, and smart furniture—driven by the rise of remote work and flexible spaces—present new opportunities for transformation. This study proposes development strategies for emerging markets focused on technological adoption, green manufacturing, and digital sales models. Findings offer valuable insights not only for the restructuring of China’s office furniture sector but also for guiding industrial upgrading in other developing economies.